2023
DOI: 10.1007/s00464-023-09878-y
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the magnetic sphincter augmentation device: an assessment of etiology, clinical presentation, and management

Abstract: Background Magnetic sphincter augmentation (MSA) erosion, disruption or displacement clearly requires device removal. However, up to 5.5% of patients without anatomical failure require removal for dysphagia or recurrent GERD symptoms. Studies characterizing these patients or their management are limited. We aimed to characterize these patients, compare their outcomes, and determine the necessity for further reflux surgery. Methods This is a retrospective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…However, we previously published our experience with MSA removal and found that the indications for removal were persistent dysphagia (78%) followed by inadequate control (22%). 27 In our experience, no patients have required device removal for GBS. Therefore, we recommend watchful waiting with lifestyle modification and medications for the management of GBS.…”
Section: Discussionmentioning
confidence: 76%
“…However, we previously published our experience with MSA removal and found that the indications for removal were persistent dysphagia (78%) followed by inadequate control (22%). 27 In our experience, no patients have required device removal for GBS. Therefore, we recommend watchful waiting with lifestyle modification and medications for the management of GBS.…”
Section: Discussionmentioning
confidence: 76%
“…In a retrospective study of 425 patients with a removal rate of 5.5%, Tatum et al (15) suggested to avoid additional intervention and to redo an MSA implant or perform fundoplication only in patient with malposition of the device or hiatal hernia. In a recent study, removal for dysphagia yielded excellent outcomes regardless of concurrent antireflux repair, whereas patients with persistent GERD had worse outcomes without antireflux repair ( 26). Our preference is to perform a posterior Toupet fundoplication in patients with hiatal hernia or persistent GERD, and an anterior fundoplication in patients with erosion.…”
Section: Discussionmentioning
confidence: 99%
“…15 In absence of evidence of an endoscopic or radiologic anatomical failure, a study from our center suggests that management and decision regarding revisional antireflux surgery should be tailored to the presenting symptom. 16…”
Section: Classifying Dysfunction After Magnetic Sphincter Augmentationmentioning
confidence: 99%